2011
DOI: 10.1186/ar3369
|View full text |Cite
|
Sign up to set email alerts
|

Baseline predictors of response and discontinuation of tumor necrosis factor-alpha blocking therapy in ankylosing spondylitis: a prospective longitudinal observational cohort study

Abstract: IntroductionIdentifying ankylosing spondylitis (AS) patients who are likely to benefit from tumor necrosis factor-alpha (TNF-α) blocking therapy is important, especially in view of the costs and potential side effects of these agents. Recently, the AS Disease Activity Score (ASDAS) has been developed to assess both subjective and objective aspects of AS disease activity. However, data about the predictive value of the ASDAS with respect to clinical response to TNF-α blocking therapy are lacking. The aim of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
147
3
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(175 citation statements)
references
References 22 publications
16
147
3
9
Order By: Relevance
“…Although the current study did not evaluate the reasons patients switched or discontinued TNFi therapy, previous studies have shown that approximately 30-36% of patients with AS, discontinued or switched biologic therapy because of adverse events [35,36] or lack of treatment effect [37]. Although no specific TNFi has been shown to be more effective than another in patients with AS [12,38], studies of TNFi treatment patterns provide better understanding of real-world use.…”
Section: Add-on Medication N (%)mentioning
confidence: 99%
“…Although the current study did not evaluate the reasons patients switched or discontinued TNFi therapy, previous studies have shown that approximately 30-36% of patients with AS, discontinued or switched biologic therapy because of adverse events [35,36] or lack of treatment effect [37]. Although no specific TNFi has been shown to be more effective than another in patients with AS [12,38], studies of TNFi treatment patterns provide better understanding of real-world use.…”
Section: Add-on Medication N (%)mentioning
confidence: 99%
“…Regarding other concomitant agents, steroid use at enterocutaneous fistula onset has been reported to be a negative predictor of anti-TNF failure (9). Moreover, a higher level of CRP is reported to be a significant negative predictor in patients treated with biological agents, although these reports describe patients with rheumatoid arthritis and ankylosing spondylitis (19,20). Interestingly, in this case series, the two cases that failed to achieve fistula closure did not receive azathioprine, and the case that showed sustained complete remission of the fistula received concomitant azathioprine; additionally, the initial CRP level of case 3 was the lowest among these three patients.…”
Section: Discussionmentioning
confidence: 76%
“…Curkendall et al 6 também encontraram associação do sexo feminino à alta taxa de não adesão aos biológicos adalimumabe e etanercepte. As razões para a menor taxa de não adesão entre os homens ainda é desconhecida 27 . Entretanto, em uma revisão sistemática que identificou fatores associados à adesão no tratamento da artrite reumatoide 26 , o sexo apresentou associação conflitante.…”
Section: Discussionunclassified